ADOÇÃO DE PRÁTICAS DE SUSTENTABILIDADE NAS INDÚSTRIAS DE CERÂMICA VERMELHA DO MUNICÍPIO DE PRUDENTÓPOLIS-PR - Kuasoski, Marli (2016)
The aim of this work is to identify and analyze the practice of sustainability that was embraced by the red pottery industries in Prudentopolis-PR. In this case, it were used the descriptive methodology procedure, bibliography and recollecting data, and a quantitative and qualitative methodology to approach the problem. The main outcomes indicate that in the Parana Prudentopolis County, the red pottery sector is economically meaningful, due to the market scope in different counties of Parana, which brings forth jobs and profit. The environmental impact is a consequence of the clay extraction and transport; though, there are proper techniques of extraction and recovery of the degraded area, which can alleviate the situation at least partially and in a long term. The study exhibits that in spite of the managers` worries of the investigated companies, not all the procedures considered essential to recover the explored area are executed.Relating to social aspects, the results of the study shows that the main concern of the companies is the workers` salaries because of lack of qualified manpower. But the major impact that reaches the community are those related to the natural landscape, which was affected by noise and dust that cause disturbance to people who live close to the deposits, consequently bring out conflicts between both parts.